Selección de un método para la evaluación del impacto social usando AHP - Delgado, Alexi (2018)
Increase of socio-environmental conflicts during the planning or execution of projects makes social impact assessment is increasingly necessary and objective in order to prevent potential social conflicts. In this paper, we present a study to select the best alternative methodology available and applicable to social impact assessment (SIA) on projects and programs. The selection was conducted using the methodology of analytic hierarchy process (AHP). In this study four alternative methods for social impact assessment were proposed: Delphi, AHP, FAHP and Grey clustering, which were ranked according to criteria: Quantification, robustness and standardization. To make the selection using AHP, we provided of a panel of four experts selected for this study. The results showed that the best method for social impact assessment is the Grey clustering complemented with Delphi method and other qualitative procedures during field study and data collection.